Enhancing the Achievement of Learning Outcomes for Foreign Language Learners Based on Gamification and Card Games - Yasmeen Alomair; Salah Hammami (International Journal of Computer Games Technology)
Gamification and card games have gained increased popularity across diverse educational domains, particularly in the field of foreign language learning (FLL). They offer potent tools that can transform the learning process into an engaging, interactive, and enjoyable experience. Currently, numerous instances of gamified or card game–based language learning methods have demonstrated their significant impact on sustaining learners’ engagement and advancing their proficiency levels. However, it is noteworthy that these approaches often prioritize the motivational aspect while neglecting the imperative need to enhance student learning outcomes (SLOs). The latter holds pivotal importance not only in determining the success of academic courses but also in evaluating the effectiveness of e-content. To address this gap, the primary objective of this work is to enhance the achievement of SLOs within the context of foreign language courses. A novel framework is proposed for learning foreign languages, harnessing the potential of gamification and card games. This framework, developed through the integration of contemporary technologies used in e-learning systems and foreign language applications, encompasses agent technology and the microlearning strategy. A case study was conducted to evaluate the effectiveness of the proposed framework. The results revealed a statistically significant improvement in SLOs. This study contributes significantly to the advancement of both gamification and game-based learning, presenting a promising pedagogical paradigm for language teaching and learning.